Dynamic constitutional frameworks for DNA biomimetic recognition. Issue 11 (11th December 2014) - Catana, Romina; Barboiu, Mihail; Moleavin, Ioana; Clima, Lilia; Rotaru, Alexandru; Ursu, Elena-Laura; Pinteala, Mariana
Abstract : The strategy presented here can be used to self-generate dynamic constitutional networks for the systematic rationalization of active delivery systems. It leaves the possibility of DNA to self-select and self-generate the most adapted carrier for its own active and optimal transfection. Abstract : Linear and cross-linked dynamic constitutional frameworks generated from reversibly interacting linear PEG/core constituents and cationic sites shed light on the dominant coiling versus linear DNA binding behaviours, closer to the histone DNA binding wrapping mechanism.